Production, Marketing And Future Prospects of Kiwifruit in Nepal - Sharma, Anup; Thapa, Sulochana; Khatiwada, Mohan Prasad (International Journal of Applied Sciences and Biotechnology, 2020)
Kiwifruit is one of the leading agriculture commodities having tremendous potential of export to the international market. Nepal offers suitable topography, climate and soil for profitable production of kiwifruit having unique taste, precocity and high nutritive and medicinal values. This study attempts to analyze the production trend, export and import, current scenario and future prospects of kiwifruit in Nepal. Findings shows that the production of kiwifruit is in increasing trend with an average annual growth rate of 46.5% from fiscal year 2014/15 to 2016/17 in Nepal. The commercialization of Nepalese kiwifruit is still in the state of infancy. Even though possessing passable shot in local and the global market, country yet produces small-scale of kiwifruit. The main challenges include inadequate scientific research on kiwifruit, lack of adoption of improved technology, insufficient investment, and poor-quality planting material, unstable prices and profit margins along with inappropriate market channels. Thus, to fortify kiwifruit subsector, it is recommended to focus on strategy of improving kiwifruit productivity with conventional mechanization, improved technology adoption, price intervention, market recognition, establishment of storage and processing centers and diplomatic relations for convenient global marketing.Int. J. Appl. Sci. Biotechnol. Vol 8(2): 179-186